2023
DOI: 10.1186/s12957-023-02901-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of resection margin width in patients with intrahepatic cholangiocarcinoma: a meta-analysis

Abstract: Background Some studies have pointed out that a wide resection margin can improve the prognosis of intrahepatic cholangiocarcinoma, but some researchers disagree and believe that a wide margin may increase complications. The optimal margin length of intrahepatic cholangiocarcinoma is controversial. Method The literature was searched in PubMed, MedLine, Embase, the Cochrane Library, and Web of Science until December 31, 2021, to evaluate the postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…A histologically positive resected margin is a risk factor in the prognosis of ICC patients. [17,18] It is generally believed that it is more difficult to assess the prognosis of ICC patients with R0 resected margins after surgery. However, the results of this study showed that CA125 had a significant ability to predict the prognosis of ICC patients.…”
Section: Discussionmentioning
confidence: 99%
“…A histologically positive resected margin is a risk factor in the prognosis of ICC patients. [17,18] It is generally believed that it is more difficult to assess the prognosis of ICC patients with R0 resected margins after surgery. However, the results of this study showed that CA125 had a significant ability to predict the prognosis of ICC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, margin width has been independently associated with recurrence-free and overall survival with margins less than one centimeter associated with poorer survival as compared to larger margins [23]. A meta-analysis that included a total of 3007 patients from eleven studies found that achieving a margin width of more than five or ten millimeters was significant in improving survival [24]. While parenchymal-sparing resections have been well-established in the surgical treatment of HCC and colorectal liver metastases, the impact of nonanatomic resection for ICC on long-term outcomes remains debated [25,26].…”
Section: Surgical Managementmentioning
confidence: 99%
“…Free surgical margin is a well described factor influencing recurrencefree survival (RFS) and overall survival (OS). Indeed, positive margin status was identified as strong factors for unfavourable prognosis in patients underwent resection (15,16). Moreover, surgical margins <1 cm is linked to worse prognosis compared to margin more than 1 cm (17).…”
Section: Curative Surgerymentioning
confidence: 99%